2019
DOI: 10.13189/ujer.2019.071607
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Problem-based Learning – Flipped Classroom Model in Chemistry and Its Effect on Scientific Literacy

Abstract: This study aims to determine the effect of the problem-based learning-flipped classroom model and critical-thinking skills toward students' scientific literacy on the topic of reaction rates. The implementation of the problem-based learning-flipped classroom model is considered appropriate for developing students' criticalthinking skills and scientific literacy. The learning time in the classroom becomes more effective and through a problem-solving process, the students can develop critical-thinking skills, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
1
4
0
3
Order By: Relevance
“…Through the active engagement, pre-service teachers in the experimental class developed more conceptual understanding and developed thinking skills that enabled them to move beyond understanding to knowledge application and synthesis. The finding is similar to previous studies that find FIBL could promote creativity, critical thinking and problem-solving skills in chemistry (Karyadi et al, 2020;Paristiowati et al, 2019). It can be concluded that flipped classroom and inquiry-based learning are effective learning approaches that enhance knowledge development of new skills that facilitate learning real-life problems.…”
Section: Discussionsupporting
confidence: 88%
“…Through the active engagement, pre-service teachers in the experimental class developed more conceptual understanding and developed thinking skills that enabled them to move beyond understanding to knowledge application and synthesis. The finding is similar to previous studies that find FIBL could promote creativity, critical thinking and problem-solving skills in chemistry (Karyadi et al, 2020;Paristiowati et al, 2019). It can be concluded that flipped classroom and inquiry-based learning are effective learning approaches that enhance knowledge development of new skills that facilitate learning real-life problems.…”
Section: Discussionsupporting
confidence: 88%
“…A study showed that experiential learning by conducting project-based learning could increase the students motivation and performance in many levels of academics. For example, in junior high school and senior high school (Pamungkas et al, 2020;Paristiowati et al, 2019), and the higher education level (Nargundkar et al, 2014) by comparing the before and the after students abilities.…”
Section: Previous Studymentioning
confidence: 99%
“…Penggabungan model dan pendekatan pembelajaran tersebut bertujuan untuk mengoptimalkan proses pembelajaran dengan menggabungkan keunggulan dari keduanya. PBL merupakan model pembelajaran siswa aktif yang memberikan dampak positif dalam meningkatkan hasil belajar, bekerja sama dalam kelompok, belajar mandiri, berpikir kritis, kemampuan pemecahan masalah, kreativitas, dan kolaborasi (Mühlfelder & Chandrasekaran, 2015;Paristiowati et al, 2019;Wijaya, 2021;Wijayanti et al, 2020). PBL melatih siswa untuk menemukan pengetahuannya melalui elaborasi pemecahan masalah yang dihadapi, menstimulasi siswa untuk berekplorasi dan belajar bersama dalam kelompok serta berkolaborasi dalam memecahkan masalah (Rahmawati et al, 2021).…”
Section: Pendahuluanunclassified